Replacement of LVDS to HVDS for Reduction in Distribution Losses, Improvement in Voltage Profiles and Economic Analysis for National Saving - Chauhan, Rajeev K.; Maurya, Sanjay Kumar; Chauhan, Durg Singh (Recent Advances in Electrical & Electronic Engineering, 2023)
Introduction: Rural electrification in India is planned with high-capacity distribution transformers which supply the isolated location loads of various categories like agricultural, household, small business, etc. This distribution system planning with non-optimal distribution transformers leads to poor voltage profiles and high power losses in the distribution network. This paper presents that a High-Voltage Distribution System (HVDS) is more suitable than a Low- Voltage Distribution System (LVDS). Methods: A model is developed to evaluate the technical losses, voltage profiles, and optimal payback period of the investments for the planned HVDS network. The replacement of LVDS with HVDS is achieved by replacing high-capacity distribution transformers with small-capacity at optimal locations. Results: The results of this study are validated on the real 11kV agricultural feeder of the Narshinghpur District of Madhya Pradesh, India. Conclusion: The results demonstrate improvement in voltage profiles, low power losses, and optimal payback period for the proposed problem. The obtained results proved that the replacement of LVDS with HVDS would be more beneficial for rural electric power distribution system planning.
Keywords: low-voltage distribution system